MENINGKATKAN KEMAMPUAN PENALARAN DAN PRESTASI MATEMATIKA DENGAN PENDEKATAN KONSTRUKTIVISME PADA SISWA SEKOLAH MENENGAH ATAS - Bambang Riyanto; Rusdy A. Siroj (Jurnal Pendidikan Matematika, 2011)
The research aims are to know (1) the effect of learning approach toward mathematics echievement, (2) the effect of reasoning level student’s toward mathematics echievement, and (3) intraction between learning approach and reasoning level student’s toward mathematics echievement. The research method that be used is experiment research. Collecting data is conducted by reasoning test and echievement mathematics test. The research is experimented at Senior High School number 1 Kayuagung. Population of research  is all student at tenth class grade that involve 7 class. The sample are class X.A  that involve 31 student as experiment class and X.B that involve 31 student as control class. The research show that the Anova two way for approach learning is obtained F hitung = 15,982 and Ftabel=4,02, so F hitung > F tabel, or the mathematics echievement student that be following at constructivism approach is better than at conventional approach. The anova two way for level reasoning student’s is obtained F hitung = 39,489 and Ftabel=4,02, so Fhitung> F tabel, or The students that have high level reasoning is better than the students that have low level reasoning. The analysis of two way Anova for interaction between the approach learning and the level reasoning student’s is obtained F hitung = 0,265 and Ftabel=4,02, so F hitung < Ftabel, or there isn’t interaction between  learning approach and the level reasoning student’s  to reach mathematics echievement.Keywords: Learning Approach, Mathematical Reasoning and Mathematics Echievement